Strategi dan Implementasi Penyusunan Soal Higher Order Thinking Skills (HOTS) Bagi Guru Sekolah Dasar di Kabupaten Kebumen - Suhartono Suhartono; Tri Saptuti Susiani; Moh Salimi; Ratna Hidayah (DEDIKASI: Community Service Reports, 2020)
One element of the 2013 curriculum transformation at the elementary school level is the improvement of the learning process and the application of integrated thematic using scientific and familiar development of higher order thinking skills (HOTS) for students. To make this happen, elementary school teachers must have competence in planning, implementing, and evaluating learning that focuses on HOTS, but those who for the most part do not understand and apply. PKM is expected to be able to provide an understanding of teachers in conducting learning and encouraging students in higher-order aspects of thinking. The PKM was held at the teacher working group (KKG) forum which was held once for four meetings. The strategy used was an explanation of the HOTS concept, discussion of the development of indicators of basic competencies (KD), a lattice preparation workshop and problem solving rules, and preparation of questions that support HOTS. From the results that have been done, it can be concluded that a small number of elementary school teachers have done learning and penances that do HOTS; This activity can broaden teachers' insights so that they can produce outcomes consisting of lattices and the development of HOTS questions on thematic learning that addresses the main areas of PKN, Indonesian Language, Social Sciences, Natural Sciences, and Mathematics.